Developing the Content of Webtoon Comic Application as Supporting Media in Learning English Grammar at the 2nd Semester English Students of IAIN Palopo - Ariel, Muhammad; Sahraini, Sahraini; Furwana, Dewi (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research aims to create a supporting media product in English Grammar learning in semester 2 students majoring in English at IAIN Palopo. based on observations in June 2019, the author found a problem in the scale of student use in smartphone use that is increasingly growing. Therefore, the author is interested in creating an online comic that can be accessed on the phone by using an application called Webtoon. The study design used in this study was Research and Development (R&D) utilized ADDIE Model. It consists of Analyze, Design, Develop, Implement, and Evaluate. The product is used as a supporting medium in English grammar learning which was once being studied by Semester 2 English Student IAIN Palopo. The product was tried out to the Students of Semester 2 of English Students at IAIN Palopo. The instruments were used in this study are Questionnaire for need analysis and observation sheet for 5 Experts and student’s perception. In this study, 5 experts were involved in order to validate the product. The elements of the validation are Display, Content/Materials, Language, and the Application. The result based from the expert’s validation as well as try-out product result, the product of this study was appropriate to be applied for the students of English Department semester 2, as a supporting media in Learning English Grammar